Research Submission: Gastric Stasis in Migraine: More Than Just a Paroxysmal Abnormality During a Migraine Attack - Aurora, Sheena K; Kori, Shashidhar H; Barrodale, Pat; McDonald, Susan A; Haseley, David (Headache, 2006)
Objective.-The aim of this article is to evaluate gastric motility and emptying in the ictal and interictal period in migraine. Background.-Nausea is a predominant symptom of migraine and the basis of it is thought to be gastric stasis. Objective methods to establish this are however lacking. We utilized gastric scintigraphy studies to determine gastric motility in the ictal and interictal period of migraine. Methods.-Ten migraine subjects were compared to equal number of age and sex matched controls. Gastric scintigraphy using a standard meal was performed in all control subjects once and in all 10 migraine subjects in the interictal period and nine studies were performed in the ictal period migraine. Results.-The time to half emptying was delayed in migraine ictally (78%) and interictal period (80%) using normative data at this institution. Gastric stasis was less pronounced ictally (149.9 minutes) compared to interictal period (188.8 minutes). There was a significant delay compared to nonmigrainous controls (migraine 188.8 minutes vs normal controls 111.8 minutes; P < .05). These data were replicated in percentage of radioactive material remaining in the stomach at 2 hours. Conclusions.-Contrary to previous belief, this study has demonstrated that migraineurs suffer from gastric stasis both during and outside an acute migraine attack. This may suggest that migraineurs may have an abnormal autonomic function compared to nonmigrainous controls. The potential role of this in pathophysiology of migraine is discussed and avenues for further investigations are explored.